2019
DOI: 10.1111/aogs.13760
|View full text |Cite
|
Sign up to set email alerts
|

Relative accuracy of computerized intrapartum fetal heart rate pattern recognition by ultrasound and abdominal electrocardiogram detection

Abstract: Introduction Noninvasive fetal heart rate monitoring using transabdominal fetal electrocardiographic detection is now commercially available and has been demonstrated to be an effective alternative to traditional Doppler ultrasonographic techniques. Our objective in this study was to compare the results of computerized identification of fetal heart rate patterns generated by ultrasound‐based and transabdominal fetal electrocardiogram‐based techniques with simultaneously obtained fetal scalp electrode‐derived h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“… 7 However, because the Doppler detected by the ultrasound Doppler fetal heart rate detector often contains a large amount of messy, large variability, and uneven noise, it will cause a large degree of interference to the calculation of fetal heart rate. 8 , 9 The algorithms currently used for fetal heart rate detection by ultrasound Doppler are mainly divided into autocorrelation and short-term average amplitude difference method. 10 The autocorrelation algorithm was adopted in this study to process the ultrasound Doppler of fetal heart rate, and the results showed that it can be used for the onset of fetal growth restriction during pregnancy, which provides a reference for understanding the degree of fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, because the Doppler detected by the ultrasound Doppler fetal heart rate detector often contains a large amount of messy, large variability, and uneven noise, it will cause a large degree of interference to the calculation of fetal heart rate. 8 , 9 The algorithms currently used for fetal heart rate detection by ultrasound Doppler are mainly divided into autocorrelation and short-term average amplitude difference method. 10 The autocorrelation algorithm was adopted in this study to process the ultrasound Doppler of fetal heart rate, and the results showed that it can be used for the onset of fetal growth restriction during pregnancy, which provides a reference for understanding the degree of fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative noninvasive method employs a maternal surface electrode patch to detect the FHR, maternal heart rate (MHR) and UC .7 There is strong evidence that this approach is at least as accurate and reliable as US/TOCO-based electronic fetal monitoring (EFM) in term parturients, 8,9 and that it permits accurate identification of normal and pathological FHR patterns. 10 To further characterize the role of abdominal surface-based monitoring, we compared its performance to that of US/TOCO in women with preterm contractions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For the first time, a recently reported secondary analysis [25] from the previously published parent study [9] assessed whether Monica AN24 produced FHR patterns that could be interpreted and compared to those obtained by Doppler ultrasound. The parent study [9] was undertaken on 75 labouring women at three centres and compared the two modalities of monitoring (abdominal fetal ECG and Doppler ultrasound) with fetal scalp electrode.…”
Section: Plos Onementioning
confidence: 99%
“…The study [9] showed that FHR detection using abdominal fetal ECG device was more reliable and accurate than Doppler ultrasound. For the purpose of secondary analysis [25], the authors reported data on the subset of women (n = 30) instead of including all 75 women that participated in the parent study [9]. Results of this secondary analysis [25] showed that compared to Doppler ultrasound, abdominal fetal ECG reliably reproduced the computerised FHR patterns during labour.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation